VEXAS: A review of current understandings and emerging treatment strategies - Holden, Robert; Jeelall, Yogeshraj; McLean-Tooke, Andrew; Pathmanathan, Kylan; Nolan, David (Frontiers in Immunology, 2025)
VEXAS (Vacuoles, E1 enzyme, X-linked, Autoinflammatory, Somatic) syndrome is a late-onset autoinflammatory disorder, typically affecting males, caused by somatic mutations in the X-linked gene UBA1 encoding the E1 ubiquitin-activating enzyme. These mutations result in defective ubiquitination and dysregulation of protein degradation, leading to Endoplasmic Reticulum stress and activation of innate immune pathways. This leads to significant inflammatory manifestations including fever, chondritis, neutrophilic dermatoses, and cytopenia’s and a range of inflammatory manifestations that define the clinical syndrome. Alongside these autoinflammatory manifestations, VEXAS exhibits features of clonal haematopoiesis, with clonal dominance of UBA1-mutant haematopoietic stem and progenitor cells with preferential myeloid differentiation and impaired generation of megakaryocytes, erythroid and lymphoid cells. The convergence of somatic mutation, inflammation, and bone marrow failure situates VEXAS at the interface of autoinflammation and hematologic neoplasia. Therapeutic approaches have focused on immunosuppression (e.g., corticosteroids, IL-6 inhibitors, JAK inhibitors), though these often yield only partial responses. Targeted therapies aimed at the mutant clone—including hypomethylating agents are under investigation. Allogeneic hematopoietic stem cell transplantation remains the only curative strategy. This review synthesises recent genetic, cellular, and clinical advances to consider VEXAS as an age-related proteosomopathy that unites clonal haematopoiesis with innate-immune dysregulation and provides appraisal of both established immunomodulators and emerging clone-directed therapies in addition to advocating harmonised response criteria, thereby offering a cohesive roadmap for future mechanistic studies and trial design in this rapidly evolving field.